Labor Conditions of Social Workers in Public Hospitals in the Province of Mendoza, Argentina. Background of the Investigation - Molina, Cecilia Amalia; Roslan-Angeloni, Yanina Noemi; Correa, Analía Graciela; Varela, Viviana Elena (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This paper summarizes the results of a study on decent work conditions of social workers in public hospitals in Mendoza, Argentina and details the challenges that had to be overcome by the research team as a result of its members being involved in the problem to be investigated. The methodological design is quantitative and qualitative. It combines information obtained through a self-administered questionnaire provided to professionals from six public hospitals (response rate 75%) and in-depth interviews to an intentional sample that contemplated various diversities present in the universe. Among the significant findings, it is identified that relationships between colleagues are the most privileged way to enter hospitals and that these relationships are more reliable in resolving labor conflicts in comparison with unions or health authorities. Respondents claim to enjoy high professional autonomy, but at the same time, they feel excluded from institutional policy decisions that affect them both in their work and professionally. They consider that the contributions of the discipline are valued by other members of the health teams, but, in certain situations, the theoretical frameworks and the specific proposals that these frameworks entail are a source of abuse. It concludes that the concept of decent work offers key dimensions to acknowledge the profession’s working conditions in different fields. Moreover, when the research team is part of the field of study, it is essential to exercise reflection permanently to produce rigorous and strategic information for the professional team.